The Use of Sentinel-1 Synthetic Aperture Radar (SAR) Images and Open-Source Software for Cultural Heritage: An Example from Paphos Area in Cyprus for Mapping Landscape Changes after a 5.6 Magnitude Earthquake - Tzouvaras, Marios; Kouhartsiouk, Dimitris; Agapiou, Athos; Danezis, Chris (My University, 2019)
Active satellite remote sensors have emerged in the last years in the field of archaeology, providing new tools for monitoring extensive cultural heritage landscapes and areas. These active sensors, namely synthetic aperture radar (SAR) satellites, provide systematic datasets for mapping land movements triggered from earthquakes, landslides, and so on. Copernicus, the European program for monitoring the environment, provides continuous radar datasets through the Sentinel-1 mission with an almost worldwide coverage. This paper aims to demonstrate how the use of open-access and freely distributed datasets such as those under the Copernicus umbrella, along with the exploitation of open-source radar processing software, namely the sentinel applications platform (SNAP) and SNAPHU tools, provided respectively by the European Space Agency (ESA) and the University of Stanford, can be used to extract an SAR interferogram in the wider area of Paphos, located in the western part of Cyprus. The city includes various heritage sites and monuments, some of them already included in the UNESCOWorld Heritage list. The interferogram was prepared to study the e ects of an earthquake to the buildings and sites of the area. The earthquake of a 5.6 magnitude on the Richter scale was triggered on 15 April 2015 and was strongly felt throughout the whole island. The interferogram results were based on Di erential Synthetic Aperture Radar Interferometry (D-InSAR) methodology, finding a maximum uplift of 74 mm and a maximum subsidence of 31 mm. The overall process and methodology are presented in this paper.
Keywords: Land movements; SAR interferometry; Sentinel-1; Copernicus; Cultural heritage; Decision-making; Policy; Cyprus